Limits of athletic performance by age: an analysis through the best performances in athletic jumping events - René Brenzikofer; Júlia Barreira; Denise Vaz Macedo (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aim: This study aimed to investigate and interpret the upper limit of recorded performances in the four jumping events according to the age of the athletes. Methods: A phenomenological and its corresponding mathematical model were developed to describe the age-related upper limit of performance according to sex and competition level (national or world-class), comprising 16 groups. Our model was based on three hypothesised parameters: i) a maximum performance level (Pmax) for each jumping event; ii) the rate of performance growth which is proportional to what remains to reach Pmax (constant of proportionality K); iii) a starting age (T0) for its application. The resulting exponential mathematical model integrates the three parameters, which were quantified by fitting the model to the performance data. Results: All the 16 limit curves were efficiently fitted within the upper borders of the data over the entire analysed age range. The adequacy of the model and its hypotheses were validated through the R² of the fitted curves (mean = 0.90, max/min = 0.98/0.75), and the fitting of the 48 parameters were qualified through their 95% confidence intervals. An interpretation of the model's parameters is proposed and comparisons of the age-related performance between Brazilian and international athletes are exhibited. A linear relation between To and 1/K was observed. Conclusion: The limit curves may be used as a reference for age-related improvement in athletic performance. The comparison between the limit curves of national and world-class competition levels reveals an original tool for comparing the effectiveness of the country's infrastructures and sports policies.